Factors associated with reduced risk of musculoskeletal disorders among office workers: a cross-sectional study 2017 to 2020 - Bukhari Putsa; Wattana Jalayondeja; Keerin Mekhora; Petcharatana Bhuanantanondh; Chutima Jalayondeja (BMC, 2022)
Abstract Background Prolonged sitting at work should be avoided to reduce the risks of either noncommunicable diseases (NCDs) or musculoskeletal disorders (MSDs) among office workers. A short duration of breaks in sitting every hour can reduce cardiometabolic risk factors contributing to NCDs. However, the recommendation for a break from sitting at work to reduce the risks of MSDs has not been identified. Therefore, this study aimed to determine whether breaking by changing position at work, physical activity, physical fitness, stress and sleep were associated with MSDs among office workers. Methods A cross-sectional study was conducted from 2017 to 2020. Participants aged 20-59 years and using a computer at work ≥ 4 days/week were recruited. Data were collected using an online self-reporting questionnaire for computer users and 5 domains of physical fitness tests. Odds ratio (OR) with 95% confidence interval (CI) and multivariate logistic regression were used for statistical analysis. Results Prevalence of MSDs was 37.9% (n = 207/545) and the most area of complaint were the neck, shoulders and back. A nonsignificant association between physical fitness and MSDs among office workers was obtained. After adjusting for age, sex, body mass index, and comorbidity, moderate-to-vigorous intensity physical activity (MVPA) ≥ 150 min/week and sitting at work ≥ 4 h/day were MSDs risk factors (OR = 1.57, 95%CI = 1.04-2.37). Frequently changing positions from sitting to standing or walking at work every hour could reduce the risks of MSDs by more than 30%. The risks of MSDs increased among office workers who commuted by staff shuttle bus and personal car and had high to severe stress and slept < 6 h/day (1.6 to 2.4 times). Conclusion Our findings indicated MVPA and prolonged sitting were MSD risk factors. We recommend office workers change position from sitting to standing or walking during work every hour and sleep ≥ 6 h/day to reduce risks of MSDs.